Defining the human right to energy and its normative value - Zantua, Rod Ralph Salazar (Animo Repository, 2019)
Affordable and clean energy was set as one of the Sustainable Development Goals by the United Nations in 2012. However, around 1.2 billion people still do not have access to electricity. Furthermore, there is no direct recognition of energy as a basic human right in any binding international instrument. This study sought to establish the legal grounds for the right to energy and define its normative value, as well as determine its place in customary international law. The human right to energy is not only an implied right under the ICESCR, but a standalone right altogether which needs recognition in the international community, in order to meet other related rights such as the right to housing, right to water and sanitation and the right to development. Furthermore, pursuant to recent developments aimed at sustainable development, the right to energy must not only involve access, but security, sustainability and affordability as well. However, in terms of its place in customary international law, this research points out that it is customary international law in statu nascendi or in its early stages attributable to the fact that recognition by states is fairly new, not enough to establish consistent practice. In the end, it is recommended that a codification of the right, through either a General Comment by the CESCR or through regional documents or domestic legislation be sought in order to establish opinio juris.